Efek Penambahan Tepung Daun Kelor Pada Fermentasi Tempe Terhadap Kadar Vitamin C Dan N-Amino Tempe Kelor (PELOR) - Cucuk Suprihartini; Arya Ulilalbab; Frenky Arif Budiman (JURNAL ILKES : Jurnal Ilmu Kesehatan, 2021)
Abstract Tempe is nicknamed the miracle food, this is due to the processing of soybeans into tempe through the fermentation process of rhizopus sp. The fermentation process increases protein digestibility, because it breaks down protein into simple amino acids. In addition, there is a synthesis of vitamin B12, unsaturated fatty acids, and antioxidant compounds. While the moringa leaves are nicknamed the miracle leaves, they have a high nutritional content. Moringa leaves actually contain very high amounts of vitamin A, vitamin C, vitamin B, calcium, potassium, iron and protein, which are easily digested and assimilated by the human body. Vitamin C reduces ferric iron to ferrous in the small intestine so that it is easily absorbed. By combining these two miraculous ingredients, it aims to increase the vitamin C levels in tempeh and study whether there is an effect of adding Moringa leaf flour to the n-amino levels of Moringa leaf tempe. This research is an experimental research with a completely randomized design. Treatment by adding Moringa leaf flour to soybean tempe and the dependent variables were levels of vitamin C and levels of N-Amino in tempe moringa. The concentrations of adding Moringa flour in this study were 0%, 2% and 4%. Analysis of vitamin C using iodimetric method and n-amino test using formol titration method. The average results of the vitamin C test on tempeh with the addition of Moringa leaf flour were as follows: 0% of 0.38%, 2% of 0.69% and 4% of 0.84%, the results of statistical tests with ANOVA showed a statistically significant effect. Significantly, there was a significant increase in vitamin C levels, while the results of the n-amino test were on average 0% of 0.56%, 2% of 0.72% and 4% of 0.78%, the results of statistical tests with ANOVA did not exist significant effect, but there was a tendency to increase levels of n-amino with the addition of Moringa leaf flour. The addition of Moringa leaf flour to the process of making tempeh can be another alternative to meet the needs of vitamin C. Keywords: vitamin C, N-amino, moringa leaves, tempeh